1999
DOI: 10.1021/ja9839365
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric [4 + 1] Cycloaddition of Vinylallenes with Carbon Monoxide:  Reversal of the Induced Chirality by the Choice of Metal

Abstract: Rhodium(I) and platinum(0) complexes having a chiral ligand, 1,2-bis(2,5-dialkylphosphorano)benzene, effected an asymmetric carbonylative [4 + 1] cycloaddition reaction of vinylallenes. Useful levels of asymmetric induction were attained even with substrates lacking directive heteroatom functionalities. The highest enantioselectivity of 95.0% ee was achieved in the rhodium-catalyzed reaction of a vinylallene bearing an ester group. Whereas the enantioselectivities of the rhodium-catalyzed reactions were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 21 publications
2
22
0
3
Order By: Relevance
“…Formation of η 4 -(vinylal-lene) rhodium complex 5 can initiate an oxidative cyclization to yield alkylidene metallacyclopentene 6 . This transformation has been documented in the rhodium-catalyzed [4+1] cycloaddition of vinylallenes with CO, [22] and also the corresponding alkylidene metallacyclopentene complexes were isolated and characterized in the absence of CO. [23, 24] Alkylidene metallacyclooctadiene 7 can be obtained by the cleavage of the strained cyclopropane ring in complex 6 . Reductive elimination of metallacycle 7 then yields the desired seven-membered-ring 3 .…”
mentioning
confidence: 90%
“…Formation of η 4 -(vinylal-lene) rhodium complex 5 can initiate an oxidative cyclization to yield alkylidene metallacyclopentene 6 . This transformation has been documented in the rhodium-catalyzed [4+1] cycloaddition of vinylallenes with CO, [22] and also the corresponding alkylidene metallacyclopentene complexes were isolated and characterized in the absence of CO. [23, 24] Alkylidene metallacyclooctadiene 7 can be obtained by the cleavage of the strained cyclopropane ring in complex 6 . Reductive elimination of metallacycle 7 then yields the desired seven-membered-ring 3 .…”
mentioning
confidence: 90%
“…The unique rigid structures of the chiral diamine ligands appeared to play a key role in the realization of this dual enantioselective control process. [7][8][9][10][11][12][13][14] , 修饰同一手性源衍生的手性配体 [15][16][17][18][19][20] 和改变金 属中心 [21][22][23][24][25][26][27][28][29] 来实现产物对映选择性的转变. 其中, 过渡 金属具有种类多、配位性能差异大的特点, 因而近年来, 改变手性催化剂中心金属来实现对映选择性转变的方 法逐渐引起有机化学家的关注.…”
Section: Discussionunclassified
“…However, enantiopure chiral ligands with the opposite absolute configurations are not always readily available or easy to prepare, and can be particularly problematic for ligands derived from naturally available chiral sources such as amino acids, carbohydrates and alkaloids. For this reason, several alternative methods have also been developed to induce a reversal in the enantioselectivity of a reaction by either tuning the reaction conditions (e.g., solvent, temperature and additive) [7][8][9][10][11][12][13][14], using a chiral ligand derived from a single chiral source with a modified subunit [15][16][17][18][19][20] or changing the metal center of the catalyst [21][22][23][24][25][26][27][28][29]. One of the most widely used methods for turning the enantioselectivity of a reaction involves effectively tuning the metal center of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, there are some reports that the enantioselectivity of the entire catalyst can be controlled by changing the central metal, even if the same chiral ligand is used. [27][28][29][30] In 1989, Kreuzfeld and co-workers reported that the enantioselectivity was reversed by selectively using Pt(cod) In the synthesis of optically active a-amino acid derivatives by asymmetric hydrogenation using BINAP, a chiral bisphosphine ligand developed by Noyori, rhodium and ruthenium, two transition metals with adjacent atomic numbers, show opposite enantioselectivity. 36 The chemical equation for the reversal of enantioselectivity is shown in Scheme 11.…”
Section: Control With Central Metalmentioning
confidence: 99%